The Soviet State Social Policy in the Sphere of Development of the Material Culture of the Southern Russian Peasants in the 1920-ies - Susanna D. Bagdasaryan (Centre for Behaviour and Wellness Advocacy, 2014)
This article discusses the problems of formation of the Soviet state social policy transformations in material culture of the southern Russian peasants in the 1920-ies. The necessity of studying the Soviet state social policy in Russia in the period of 1920-ies the historical aspect is determined by several factors. First, in the study of Russian history of the XX century, one of the main directions of national historiography was and remains the study of social problems at various stages of its development. In this regard, relevant is the consideration of the main challenges for social development at country and regional level. Secondly, in the formation of a new concept of social development of the country increases the need to adequate understanding of the role and importance of the Soviet state in the modernization of Russian society. One of the fundamental principles of state social policy is the principle of state responsibility for creating the conditions necessary for the development of society and the individual. In this regard, special scientific and practical interest becomes the problem of the essence of social policy in different historical periods, especially in the 1920-ies the history of the Soviet state, when it formed the Soviet system. In the analysed time clearly showed different approaches to solving social problems: in the framework of the state ideology and assumptions in Economics elements of private property (1921-1929).